The contribution of HIV infection to intracranial arterial remodeling: A pilot study. Issue 3 (15th October 2012) - Gutierrez, Jose; Elkind, Mitchell S. V.; Petito, Carol; Chung, David Y; Dwork, Andrew J.; Marshall, Randolph S
<x xml:space="preserve">Abstract</x> Pathological arterial wall changes have been cited as potential mechanisms of cerebrovascular disease in the HIV population. We hypothesize that dilatation would be present in arterial walls of patients with HIV compared to controls. Fifty‐one intracranial arteries, obtained from autopsies of five individuals with HIV infection and 13 without, were fixed, embedded, stained, and digitally photographed. Cross‐sectional areas of intima, media, adventitia and lumen were measured by preset color thresholding. A measure of arterial remodeling was obtained by calculating the ratio between the lumen diameter and the thickness of the arterial wall. Higher numbers indicate arterial dilatation, while lower numbers indicate arterial narrowing. HIV‐infected brain donors were more frequently black (80% vs. 15%, P = 0.02) compared with uninfected donors. Inter and intra‐reader agreement measures were excellent. The continuous measure of vascular remodeling was significantly higher in the arteries from HIV donors (β = 2.8, P = 0.02). Adjustments for demographics and clinical covariates strengthen this association (β = 9.3, P = 0.01). We found an association of HIV infection with outward brain arterial remodeling. This association might be mediated by a thinner media layer. The reproduction of these results and the implications of this proposed pathophysiology merits further study.